PENGARUH DEVELOPMENTAL CARE TERHADAP PENURUNAN STRES PADABAYI PREMATUR DI RUANG PERINATOLOGI RSUD Dr. HARYOTO LUMAJANG - Mariyati, Diyah Hita; Kristiawati, Kristiawati; Kurnia, Iqlima Dwi (The Indonesian Journal of Health Science, 2016)
Introduction: Stress among premature infants is a response showing inability on infants to regulate stimulus from environment which caused by maturity of nervous system, lack of physiology stability and lack of ability to cope the stress. Several ways to decrease stress among premature infants are giving infants developmental care interventions. This study aimed to describe the effect of developmental care on stress decreased among premature infants in Perinatology Room Regional General Hospital Dr. Haryoto Lumajang. Method: The design of this study was pre-experimental with one group pra-post test design, with 7 sample size who were taken by using total sampling technique. Independent variable of this study was developmental care and dependent variable was stress among premature infants. Data were taken by using observations sheet, then analyzed by using Wicoxon Sign Rank Test. Result: The result showed a significant value, p= 0,052.The result of this study can be concluded that there is influence of developmental care on stress decreased among premature infants. Discuss:  Therefore, nurses in perinatalogy room can make it as strategy and base to implement developmental care to surmount stress amon premature infants.